Buprenorphine/Naloxone for Opioid Use Disorder Among Alaska Native and American Indian People. Issue 4 (July 2021) - Lillie, Kate M.; Shaw, Jennifer; Jansen, Kelley J.; Garrison, Michelle M.
Abstract : Objectives: Opioid-related disparities are magnified among Alaska Native and American Indian (ANAI) people. Yet, no outcome studies on medication for addiction treatment, an effective treatment in other populations, among ANAI people exist. The objective of this study was to identify variables associated with buprenorphine/naloxone retention among ANAI people with opioid use disorder (OUD). Methods: The sample was 240 ANAI adults in Anchorage, Alaska who received buprenorphine/naloxone treatment for an OUD. We gathered data from the electronic health record from January 1, 2015 to December 31, 2019. We used survival analysis to explore possible predictors (demographic variables, psychiatric comorbidity, medical severity, previous opioid prescriptions, previous injury, alcohol use disorder, and co-occurring substance use) of length of treatment retention (in days) while accounting for right censoring. Results: We found that 63% of the 240 patients were retained in buprenorphine/naloxone treatment at 90 days, 51% at 6 months, and 40% at 1 year, slightly lower than the general US population. Younger age (hazard ratio 1.69, 95% confidence intervals 1.17–2.45) and co-occurring substance use (hazard ratio 2.95, 95% confidence intervals 1.99–4.38) were associated with increased rate of buprenorphine/naloxone treatment discontinuation. Conclusions: Younger patients and those with co-occurring substance use remain at higher risk of discontinuing buprenorphine/naloxone treatment for OUD in this population of ANAI people. Treatment programs serving ANAI people may consider paying special attention to patients with these characteristics to prevent treatment discontinuation. Our study highlights the need to address poly-substance use among ANAI people in treatment.